Inhaled multi-walled carbon nanotubes differently modulate global gene and protein expression in rat lungs. Issue 2 (7th February 2021) - Seidel, Carole; Zhernovkov, Vadim; Cassidy, Hilary; Kholodenko, Boris; Matallanas, David; Cosnier, Frédéric; Gaté, Laurent
Abstract: Inhalation of multi-walled carbon nanotubes (MWCNTs) induces lung inflammation. Depending on industrial applications, CNTs with different physicochemical characteristics are produced and workers can potentially be exposed. This raises concerns about the long-term health effects of these nanomaterials. Because of the wide variety of MWCNTs, it is essential to study the toxicological effects of CNTs of various shapes and to better understand the impact physical and chemical properties have on their toxicity. In this study, rats were exposed by nose-only to two pristine MWCNTs with different morphologies: the long and thick NM-401 or the short and thin NM-403. After four weeks of inhalation, animals were euthanized at four different times during the recovery period: three days (short-term), 30 and 90 days (intermediate-term) and 180 days (long-term). Analyses of the transcriptome in the whole lung and the proteome in the bronchoalveolar lavage fluid of exposed animals were performed to understand the MWCNT underlying mechanisms of toxicity. Following inhalation of NM-401, we observed a dose-dependent increase in the number of differentially expressed genes and proteins, whereas there is no clear difference between the two concentrations of NM-403. After NM-403 inhalation, the number of differentially expressed genes and proteins varied less between the four post-exposure times compared to NM-401, which supports the postulation of a persistent effect of this type of CNT. Our toxicogenomics approaches give insights into the different toxicological profile following MWCNT exposure.